Universality of weakly bound dimers and Efimov trimers close to Li-Cs Feshbach resonances - Ulmanis, Juris; Häfner, Stephan; Pires, Rico; Kuhnle, Eva; Weidemüller, Matthias; Tiemann, Enno (New journal of physics, 2015)
We study the interspecies scattering properties of ultracold Li-Cs mixtures in their two energetically lowest spin channels in the magnetic field range between 800 and 1000 G. Close to two broad Feshbach resonances (FR) we create weakly bound LiCs dimers by radio-frequency association and measure the dependence of their binding energy on the external magnetic field strength. Based on the binding energies and complementary atom loss spectroscopy of three other Li-Cs s-wave FRs we construct precise molecular singlet and triplet electronic ground state potentials using a coupled-channels calculation. We extract the Li-Cs interspecies scattering length as a function of the external field and obtain almost a ten-fold improvement in the precision of the values for the pole positions and widths of the s-wave FRs as compared to our previous work (Pires et al 2014 Phys. Rev. Lett. 112 250404). We discuss implications on the Efimov scenario and the universal geometric scaling for LiCsCs trimers.
Gesehen am 07.07.2020